2017
DOI: 10.1149/2.1871713jes
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Oxidation of the Insecticide Imidacloprid on Mixed Metal Oxide (RuO2-TiO2and IrO2-RuO2-TiO2) Anodes

Abstract: In this work, we evaluated the performance of the Ti/RuO2-TiO2 and Ti/RuO2-IrO2-TiO2 electrodes as electrocatalytic materials in the degradation of the insecticide imidacloprid (ICP). The temperature and current density operating parameters were investigated, and the degradation was followed by measurements of TOC and by UV-Vis spectroscopy. The complete oxidation de ICP (100% mineralization) was achieved by applying 40 mA cm−2 when Ti/RuO2-TiO2 or Ti/RuO2-IrO2-TiO2 were used at 60°C during 2 or 3 h electrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The primary oxidation mechanisms during EAOPs are direct electron transfer and reaction with OH • . Past research has shown that electrochemical oxidation could completely mineralize ATZ , and imidacloprid (a similar neonicotinoid insecticide to CDN). , However, these studies required extended reaction times and/or elevated temperatures (e.g., 60 °C) to achieve mineralization.…”
Section: Resultsmentioning
confidence: 99%
“…The primary oxidation mechanisms during EAOPs are direct electron transfer and reaction with OH • . Past research has shown that electrochemical oxidation could completely mineralize ATZ , and imidacloprid (a similar neonicotinoid insecticide to CDN). , However, these studies required extended reaction times and/or elevated temperatures (e.g., 60 °C) to achieve mineralization.…”
Section: Resultsmentioning
confidence: 99%
“…Among these new treatment technologies, electrochemical processes have been widely studied, mainly due to their high efficiency in the degradation of recalcitrant compounds [3,[5][6][7]. Silva et al [8] achieved complete oxidation of the insecticide imidacloprid, at a concentration of approximately 25 mg L −1 , by applying an anodic oxidation (AO) process with mixed metal oxide anodes. Successful degradation of the herbicides monolinuron, paraquat, and clopyralid and of the pesticide profenofos, at concentrations ranging 10-100 mg L −1 , by electro-Fenton (EF), was also reported [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This is an important economical aspect given the cost of ruthenium-based compounds. Due to these salient features, the conducting RuO 2 -TiO 2 heterostructure is explored in the development of supercapacitors [23], electrode for chlorine electrogeneration [28] as well as pigments, fillers, electro-resistor films for electrodes, or dielectric device catalyst supports [29,30].…”
Section: Introductionmentioning
confidence: 99%